EDUCATION OF ISLAMIC AESTHETICS FOUND IN AL-QUR’AN SURAH AR-RAHMAN - Ali Fauzi (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2020)
In Al-Qur’an Surah Ar-Rahman, The researcher finds Education of Islamic Aesthetics accumulated in figurative language. However, the Moslems just recite and do not try to know and to analyze it. The researcher chooses the title “Education of Islamic Aesthetics Found in Al-Qur’an Surah Ar-Rahman” and formulates the problem: How is the education of Islamic aesthetics found in Al-Qur’an Surah Ar-Rahman? The objective of the research is to describe the education of Islamic aesthetics he finds in Al-Qur’an Surah Ar-Rahman. The researcher hopes that this research will be useful for all sides. In order that he has knowledge about Education of Islamic Aesthethic in general and aesthetics in form of figurative language in special, he has to read many references as the basic of theories before. In the research, he uses phenomenological approach and in interpreting phenomena and facts, he uses hermeneutics. The research is qualitative research in form of content analysis and the method of research is descriptive-text analysis. The data in this research is in form of words, phrases, sentences, and verses taken from the Holy Al-Qur’an surah Ar-Rahman. The researcher collects the data by observing the text of Al-Qur’an Surah Ar-Rahman, and documenting them based on the classification of education of Islamic aesthetics accumulated in figurative language. He then analyzes the data by reducting, presenting and concluding them so that the data he uses are really valid. The researcher then describes the data of Education of Islamic aesthetics accumulated in form of figurative language he finds in the Al-Qur’an surah Ar-Rahmanelaborated in many kinds of figure of speech such as alliteration, antithesis, euphemism, personification, hyperbole, pleonasm, irony, antonomasia and apophasis. The researcher describes the data and analyzes them one by one using hermeneutics in the discussion. The researcher then concludes that in Al-Qur’an surah Ar-Rahman, he finds education of aesthetics the moslems must know. He also suggests the Moslems to recite and analyze it in order to get deep understanding on the verses and Surah Ar-Rahman.